Pre- or post-treatment with ethanol and ethyl pyruvate results in distinct anti-inflammatory responses of human lung epithelial cells triggered by interleukin-6 - Relja, Borna; Omid, Nina; Schaible, Alexander; Meier, Simon; Oppermann, Elsie; Lehnert, Mark; Marzi, Ingo; Perl, Mario (Molecular Medicine Reports, 2015)
Increased local and systemic levels of interleukin (IL)-6 are associated with inflammatory processes, including neutrophil infiltration of the alveolar space, resulting in lung injury. Our previous study demonstrated the beneficial anti-inflammatory effects of acute exposure to ethanol (EtOH) in an acute in vivo model of inflammation. However, due to its side-effects, EtOH is not used clinically. In the present study, the effects of EtOH and ethyl pyruvate (EtP) as an alternative anti-inflammatory drug prior to and following application of an IL-6 stimulus on cultured A549 lung epithelial cells were compared, and it was hypothesized that treatment with EtOH and EtP reduces the inflammatory potential of the A549 cells. Time- and dose-dependent release of IL-8 from the A549 cells was observed following stimulation with IL-6. The release of IL-8 from the A549 cells was assessed following treatment with EtP (2.5-10 mM), sodium pyruvate (NaP; 10 mM) or EtOH (85-170 mM) for 1, 24 or 72 h, prior to and following IL-6 stimulation. The adhesion capacities of neutrophils to the treated A549 cells, and the expression levels of cluster of differentiation (CD) 54 by the epithelial cells were measured. Treatment of the A549 cells with either EtOH or EtP significantly reduced the IL-6-induced release of IL-8. This effect was observed in the pre- and post-stimulatory conditions, which is of therapeutic importance. Similar data was revealed regarding the IL-6-induced neutrophil adhesion to the treated A549 cells, in which pre- and post-treatment with EtOH or EtP decreased the adhesion capacity, however, the results were dependent on the duration of incubation. Incubation durations of 1 and 24 h decreased the adhesion rates of neutrophils to the stimulated A549 cells, however, the reduction was only significant at 72 h post-treatment. The expression of CD54 was reduced only following treatment for 24 h with either EtOH or EtP, prior to IL-6 stimulation. Therefore, EtOH and EtP reduced the inflammatory response of lung epithelial cells, and the potential of EtP to mimic EtOH was observed in the pre- and post-treatment conditions.
Keywords: ethanol; ethyl pyruvate; lung; inflammation; in vitro